Influence of Integral Crystalline Waterproofing on Concrete Properties: Dosage Impact and Microstructural Analysis - Na Songkhla, Warun; Jamnam, Sittisak; Chaikaew, Chalermphol; Sua-iam, Gritsada (Salehan Institute of Higher Education, 2024)
The present research study aims to investigate the properties and performance of concrete containing an integral crystalline waterproofing (ICW) admixture, added at an optimal dosage to resist water without compromising structural integrity. To achieve this, an experimental program was conducted on specimens with ICW dosage variations ranging from 0 to 4.8 kg/m2. The impact on water absorption, pulse velocity, and microstructural characteristics was tested and analyzed using XRF and EDS techniques. The findings reveal that increasing the dosage decreases water absorption by approximately 43% at maximum dosage compared with the control. A 41% increase in pulse velocity indicates a denser concrete matrix. The principle of optimization is highlighted, as an overdose of ICW generates a non-structural crystalline gel at the bottom of the specimens. The optimum dosage range for ICW to improve water resistance without adverse effects on structural performance was determined to be 3.2 to 4.0 kg/m2. This research introduces a novel approach by evaluating the comprehensive performance of concrete in relation to ICW dosage, providing valuable insights into the practical application of ICW admixture to enhance concrete quality and durability. Doi: 10.28991/CEJ-2024-010-10-02 Full Text: PDF